Anatomical examination of the petiole of eupolypods I (Polypodiales) - JEANETTE MARA P. TAN; MARIA CELESTE BANATICLA-HILARIO; PASTOR MALABRIGO; MARJORIE DELOS ANGELES; INOCENCIO E. BUOT, JR. (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Tan JMP, Banaticla-Hilario MC, Malabrigo P, Angeles MD, JR Buot IE. 2020. Anatomical examination of the petiole of eupolypods I (Polypodiales). Biodiversitas 21: 1767-1777. The efficiency of petiole anatomy characters in identifying and describing the species and families of eupolypods I (Polypodiales) were explored. Specimens of 21 species, representing 13 genera and nine families were collected and processed in the laboratory, following proper dehydration and staining protocols. Transverse sections of the basal, median, and distal portions of the petiole were examined, photographed and analyzed. The results showed five taxonomically significant characters that can serve as family markers: (i) xylem shape, (ii) vascular bundle shape, (iii) number of vascular bundles, (iv) presence and absence of circumendodermal band, and (v) presence and absence of adaxial grooves. Based on these characters, a taxonomic key to the families of eupolypods I was constructed.